A compact BrFAFC (Bio reformed Formic Acid Fuel Cell) converting formate to power - Shin, Jong-Hwan; Jung, Namgee; Yoo, Sung Jong; Cho, Yong-Hun; Sung, Yung-Eun; Park, Tai Hyun (ROYAL SOC CHEMISTRY, 2011)
A compact BrFAFC can directly convert formate to power without hydrogen storage and poisoning effect by CO at mild temperature. We are the first to establish the performance of the BrFAFC with high power density. Furthermore, this BrFAFC can be manufactured in a simple design for use in portable fuel cells.
Keywords: HYDROGEN-PRODUCTION; CATALYSTS; ELECTROOXIDATION; GENERATION; CROSSOVER; MEMBRANE; DEHYDROGENATION; TEMPERATURE; COMPLEXES; METHANOL